An Ugi-Type Condensation of α-Isocyanoacetamide and Chiral Cyclic Imine under a New Catalytic System - Li, Sheng; Chen, Ruijiao; Liu, Xiubing; Pan, Li; Xia, Liang; Chen, Xiaochuan (Synlett, 2012)
A new catalytic Ugi-type condensation of α-isocyanoacetamide and chiral cyclic imine is developed, where the combination of phenyl phosphilic acid and trifluoroethanol is exploited to promote the Ugi-type condensation with α-isocyanoacetamide for the first time. Under this new catalytic system, the reaction using the cyclic imines as relatively inertial substrates proceed well, and chiral 3-oxazolyl-morpholin/piperazine-2-one derivatives are synthesized with high yield and stereoselectivity. Furthermore, transformation of the condensation product to a novel fused tricyclic structure is attempted initially by treatment with maleic anhydride.
Keywords: catalytic Ugi-type condensation; α-isocyanoacetamide; oxazoles; phosphilic acid; asymmetric synthesis